Construction of a pIX-modified Adenovirus Vector Able to Effectively Bind to Nanoantibodies for Targeting - Garas, M. N. (A.I. Gordeyev, 2014)
Current targeting strategies for genetic vectors imply the creation of a specific vector for every targeted receptor, which is time-consuming and expensive. Therefore, the development of a universal vector system whose surface can specifically bind molecules to provide efficient targeting is of particular interest. In this study, we propose a new approach in creating targeted vectors based on the genome of human adenovirus serotype 5 carrying the modified gene of the capsid protein pIX (Ad5-EGFP-pIX-ER): recombinant pseudoadenoviral nanoparticles (RPANs). The surfaces of such RPANs are able to bind properly modified chimeric nanoantibodies that specifically recognize a particular target antigen (carcinoembryonic antigen (CEA)) with high affinity. The efficient binding of nanoantibodies (aCEA-RE) to the RPAN capsid surfaces has been demonstrated by ELISA. The ability of the constructed vector to deliver target genes has been confirmed by experiments with the tumor cell lines A549 and Lim1215 expressing CEA. It has been shown that Ad5-EGFP-pIX-ER carrying aCEA-RE on its surface penetrates into the tumor cell lines A549 and Lim1215 via the CAR-independent pathway three times more efficiently than unmodified RPAN and Ad5-EGFP-pIX-ER without nanoantibodies on the capsid surface. Thus, RPAN Ad5-EGFP-pIX-ER is a universal platform that may be useful for targeted gene delivery in specific cells due to “nanoantibody–modified RPAN” binding.